2018
DOI: 10.1080/1028415x.2018.1557385
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 PUFAs and vitamin D co-supplementation as a safe-effective therapeutic approach for core symptoms of autism spectrum disorder: case report and literature review

Abstract: Introduction: Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders characterized by abnormal development of cognitive, social, and communicative skills. Although ASD aetiology and pathophysiology are still unclear, various nutritional factors have been investigated as potential risk factors for ASD development, including omega-3 polyunsaturated fatty acids (PUFAs) and vitamin D deficiency. In fact, both omega-3 PUFAs and vitamin D are important for brain development and function. Case repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…Two studies were included in the overall interpretation but not included in the meta-analysis due to the use of an assessment tool not used by the others 18,19 . The reasons for excluding the 14 full texts were as follows: 8 did not answer our systematic review question [20][21][22][23][24][25][26][27] , 1 was retracted by the journal due to incorrect data 28 , 2 were case reports 29,30 and 3 were open-label trials [31][32][33] . The screening and selection of the studies are presented in the PRISMA flowchart shown in Figure 1.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…Two studies were included in the overall interpretation but not included in the meta-analysis due to the use of an assessment tool not used by the others 18,19 . The reasons for excluding the 14 full texts were as follows: 8 did not answer our systematic review question [20][21][22][23][24][25][26][27] , 1 was retracted by the journal due to incorrect data 28 , 2 were case reports 29,30 and 3 were open-label trials [31][32][33] . The screening and selection of the studies are presented in the PRISMA flowchart shown in Figure 1.…”
Section: Search Results and Study Selectionmentioning
confidence: 99%
“…Exogenous vitamin D supplementation can have beneficial effects in ASD children and improve signs and symptoms of ASD [145,146], and the American Academy of Pediatrics recommends vitamin D supplementation during infancy and childhood [147]. However, a recent randomized placebo-controlled trial underlined that vitamin D supplementation had limited beneficial effects on children with ASD without any effect on the primary outcome [148].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Moreover, the AA/EPA ratio has been shown to be a reliable surrogate marker of omega-6/omega-3 ratio that may serve as a more specific indicator of the magnitude of cellular inflammation and, in turn, CV risk. An AA/EPA ratio between 1.5 and 3 has been suggested as the optimal range in order to reduce cellular inflammation and achieve beneficial effects in different clinical settings [169,170,171,172,173], although larger mechanistic and prospective studies are needed to confirm this hypothesis in the context of CVD and, specifically, VCID. Also, different measurements of AA/EPA ratio have been used across studies, basing on the levels of erythrocyte fatty acids, phospholipid fatty acids, adipose tissue fatty acids, or serum fatty acids.…”
Section: Novel Personalized Strategies To Prevent Atherosclerosismentioning
confidence: 99%